Una causa rara de absceso hepático en un país occidental - Liliana Torres; Diana Pereira Anjos (Sociedade Galega de Medicina Interna, 2019)
Klebsiella pneumoniae is a common cause of pyogenic liver abscess in patients with diabetes mellitus, preexisting hepatobiliary disease and those from Southeast Asia1. But, in the last decades, an increasingly number of cases has been reported in Western countries2. A 61-year-old portuguese male, without significant past medical history, was admitted with right upper quadrant abdominal pain and fever. He denied any recent foreign travel. Laboratory analysis showed 6900 leucocytes, C-reactive protein 287.5 mg/L, total billirubin 1.1 mg/dL, AST 116 UI/L, ALT 88 UI/L, alkaline phosphatase 180 UI/L. Abdominal Computed Tomography (CT) scan revealed a 3.4x3.3cm complex mass in the IV hepatic segment with multiple septations. Blood cultures grew Klebsiella pneumoniae and, according to the antibiogram, he was placed on ceftriaxone for 21 days. The abscess was drained by interventional radiology and gram stain and cultures of pus were positive for Klebsiella pneumoniae. His clinical condition improved and a follow-up CT, after antibiotic therapy, showed complete resolution of liver abscess. References 1. Lederman ER, Crum NF. Pyogenic liver abscess with a focus on Klebsiella pneumoniae as a primary pathogen: an emerging disease with unique clinical characteristics. AM J Gastroenterol. 2005 Feb;100(2):322-31. 2. Rahimian J, Wilson T, Oram V, Holzman RS. Pyogenic liver abscess: recent trends in etiology and mortality. Clin Infect Dis 2004, 39: 1654-1659.